Decline in cellular function of aged mouse c‐kit+ cardiac progenitor cells. (18th August 2017) - Castaldi, Alessandra; Dodia, Ramsinh Mansinh; Orogo, Amabel M.; Zambrano, Cristina M.; Najor, Rita H.; Gustafsson, Åsa B.; Heller Brown, Joan; Purcell, Nicole H.
Abstract : Key points: While autologous stem cell‐based therapies are currently being tested on elderly patients, there are limited data on the function of aged stem cells and in particular c‐kit + cardiac progenitor cells (CPCs). We isolated c‐kit + cells from young (3 months) and aged (24 months) C57BL/6 mice to compare their biological properties. Aged CPCs have increased senescence, decreased stemness and reduced capacity to proliferate or to differentiate following dexamethasone (Dex) treatment in vitro, as evidenced by lack of cardiac lineage gene upregulation. Aged CPCs fail to activate mitochondrial biogenesis and increase proteins involved in mitochondrial oxidative phosphorylation in response to Dex. Aged CPCs fail to upregulate paracrine factors that are potentially important for proliferation, survival and angiogenesis in response to Dex. The results highlight marked differences between young and aged CPCs, which may impact future design of autologous stem cell‐based therapies. Abstract: Therapeutic use of c‐kit + cardiac progenitor cells (CPCs) is being evaluated for regenerative therapy in older patients with ischaemic heart failure. Our understanding of the biology of these CPCs has, however, largely come from studies of young cells and animal models. In the present study we examined characteristics of CPCs isolated from young (3 months) and aged (24 months) mice that could underlie the diverse outcomes reported for CPC‐based therapeutics. We observed morphological differences and altered senescence indicated by increased senescence‐associated markers β‐galactosidase and p16 mRNA in aged CPCs. The aged CPCs also proliferated more slowly than their young counterparts and expressed lower levels of the stemness marker LIN28. We subsequently treated the cells with dexamethasone (Dex), routinely used to induce commitment in CPCs, for 7 days and analysed expression of cardiac lineage marker genes. While MEF2C, GATA4, GATA6 and PECAM mRNAs were significantly upregulated in response to Dex treatment in young CPCs, their expression was not increased in aged CPCs. Interestingly, Dex treatment of aged CPCs also failed to increase mitochondrial biogenesis and expression of the mitochondrial proteins Complex III and IV, consistent with a defect in mitochondria complex assembly in the aged CPCs. Dex‐treated aged CPCs also had impaired ability to upregulate expression of paracrine factor genes and the conditioned media from these cells had reduced ability to induce angiogenesis in vitro . These findings could impact the design of future CPC‐based therapeutic approaches for the treatment of older patients suffering from cardiac injury. Key points: While autologous stem cell‐based therapies are currently being tested on elderly patients, there are limited data on the function of aged stem cells and in particular c‐kit + cardiac progenitor cells (CPCs). We isolated c‐kit + cells from young (3 months) and aged (24 months) C57BL/6 mice to compare their biological properties. Aged CPCs have increased senescence, decreased stemness and reduced capacity to proliferate or to differentiate following dexamethasone (Dex) treatment in vitro, as evidenced by lack of cardiac lineage gene upregulation. Aged CPCs fail to activate mitochondrial biogenesis and increase proteins involved in mitochondrial oxidative phosphorylation in response to Dex. Aged CPCs fail to upregulate paracrine factors that are potentially important for proliferation, survival and angiogenesis in response to Dex. The results highlight marked differences between young and aged CPCs, which may impact future design of autologous stem cell‐based therapies.